Reflexive Narrative in Lolita by Vladimir Nabokov - Barreras Gómez, Asunción (Miscelánea: A Journal of English and American Studies, 1995)
What Nabokov’s narrators produce is not a faithful record of the past but an imaginative invention, mediated by their point of view, their metafictional consciousness and their active manipulation of the story. There is, then, a difficulty in portraying reality, because any point of view on reality is a subjective one, in which memory and imagination are mixed. Nabokov recognizes that he cannot show reality in a simple form. An analysis of the narration in Lolita shows a more problematic relationship between fiction and reality than the one realist fiction allows the reader to acknowledge.